The comparison of 0.05% sodium fluoride and 0.2% chlorhexidine usage and aquadest to the plaque index on fixed orthodontic patients - Wiraja, Veronica Vera D.; Hambali, Tono S.; Lambri, Soertini E. (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2007)
The fixed orthodontic appliance will cause changes in microbial flora the oral cavity and food debris accumulation and will be formed especially around the gingival sulcus. Plaque control using chemical means can be done by using mouth rinse. This research compared the influence of 0.05% sodium fluoride mouth rinse with aquadest and 0.2% chlorhexidine to the plaque index in fixed orthodontic patients. A double-blind and cross over clinical assessment were applied using a sample size of 16 male fixed orthodontic patients with the age above 21 years. 0.05% sodium fluoride, 0.2% chlorhexidine mouth rinse was given to all patients as a positive control and aquadest as a negative control. Plaque index was then measured after 24 hours without tooth brushing, after using the mouth rinse and a week after using the mouth rinse with tooth brushing. The results showed that the use of 0.05% sodium fluoride mouth rinse reduced plaque index more significantly compared to 0.2% chlorhexidine. The mechanical plaque control by tooth brushing is still the most influential mean to reduce plaque index in fixed orthodontic patients. Mouth rinse is just an additional mean to reduce plaque.